In Vitro and In Vivo Studies for the Investigation of γ-Globin Gene Induction by Adhatoda vasica: A Pre-Clinical Study of HbF Inducers for β-Thalassemia - Iftikhar, Fizza; Rahman, Saeedur; Khan, Muhammad Behroz Naeem; Khan, Kanwal; Khan, Muhammad Noman; Uddin, Reaz; Musharraf, Syed Ghulam (Frontiers in Pharmacology, 2022)
Fetal hemoglobin (HbF) is a potent genetic modifier, and the γ-globin gene induction has proven to be a sustainable therapeutic approach for the management of β-thalassemia. In this study, we have evaluated the HbF induction ability of A. vasica in-vitro and in-vivo, and the identification of potential therapeutic compounds through a bioassay-guided approach. The in-vitro benzidine-Hb assay demonstrated strong erythroid differentiation of K562 cells by A. vasica extract. Subsequently, an in-vivo study with an aqueous extract of A. vasica (100 mg/Kg) showed significant induction of the γ-globin gene and HbF production. While in the acute study, the hematological and biochemical indices were found to be unaltered at a lower dose of A. vasica. Following the bioassay-guided approach two isolated compounds, vasicinol (1) and vasicine (2) strongly enhanced HbF levels and showed prominent cellular growth kinetics with ample accumulation of total hemoglobin in K562 cultures. High HbF levels were examined by immunofluorescence and flow cytometry analysis, concomitant with the overexpression in the γ-globin gene level. Compound 1 (0.1 µM) and compound 2 (1 µM) resulted in a greater increase in F-cells (90% and 83%) with marked up (8-fold and 5.1-fold) expression of the γ-globin gene, respectively. Molecular docking studies indicated strong binding affinities of the (1) and (2) with HDAC2 and KDM1 protein that predict the possible mechanism of compounds in inhibition of these epigenetic regulators in the γ-globin gene reactivation. Altogether, these observations demonstrated the therapeutic usefulness of A. vasica for foster HbF production in clinical implications for blood disorders.